In vivo Mechanisms of Antibody-Mediated Neurological Disorders: Animal Models and Potential Implications - Giannoccaro, Maria Pia; Wright, Sukhvir K.; Vincent, Angela (Frontiers in Neurology, 2020)
Over the last two decades, the discovery of antibodies directed against neuronal surface antigens (NSA-Abs) in patients with different forms of encephalitis has provided a basis for immunotherapies in previously undefined disorders. Nevertheless, despite the circumstantial clinical evidence of the pathogenic role of these antibodies in classical autoimmune encephalitis, specific criteria need to be applied in order to establish the autoimmune nature of a disease. A growing number of studies have begun to provide proof of the pathogenicity of NSA-Abs and insights into their pathogenic mechanisms through passive transfer or, more rarely, through active immunisation animal models. Moreover, the increasing evidence that maternal antibodies to neuronal surface antigens in the maternal circulation can reach the foetal brain parenchyma during gestation, causing long-term effects, has led to models of antibody-induced neurodevelopmental disorders. This review summarises the different methodological approaches and the results of the animal models of NMDAR, LGI1, CASPR2 and AMPAR antibody-mediated disorders and discuss the results and the limitations. We also summarise recent experiments that demonstrate that maternal antibodies to NMDAR and CASPR2 antibodies can alter development in the offspring with potential life-long susceptibility to neurological or psychiatric disorders.